Adaptive stated preference analysis of shippers' transport and logistics choice - Rico Maggi; Simona Bolis (European Regional Science Association (ERSA), 1998)
In this paper we propose a micro analysis of freight transport demand. Current research concentrates with few exceptions on shippers? choice of a transport mode and offers consistent evidence on the importance of characteristics. However, with globalised production and liberalisation, the market offers services which range from simple movement to integrated logistics. As a consequence, shippers? behaviour is conceived here as a complex decision which considers transport mode choice as only a part of a firm?s logistics strategy. Since there exists no data to directly estimate the marginal willingness to pay for different qualities of transport and logistics services a stated preference approach is applied. Adaptive stated preference experiments are performed and completed by background information on long term logistics strategy. Here, we present first results combining the outcome of choice analysis with evidence on the cases from which the data has been collected.
Keywords: 330